BRIÓFITAS DO PARQUE ESTADUAL DO MIRADOR, MARANHÃO, BRASIL - CARVALHO, Francimária Vasconcelos (2024)
Maranhão houses approximately 19% of its territory in Conservation Units (CUs) and 13% of these units are in the Cerrado biome, while more than 30% of the Amazonia Maranhense region is covered by UCs. The flora of these UCs is still little known, especially with regard to the bryophyte group, which is generally neglected in floristic surveys. The Mirador State Park (PEM) fits into this aspect. It is the largest UC in Maranhão and for which only one study on bryophytes was carried out, restricted to a few collections, reflecting a possibly underestimated diversity compared to other areas of the Cerrado already studied in Maranhão. The objective of this work is to investigate the richness and composition of bryophyte communities in Mirador State Park, in the state of Maranhão, Brazil, contributing to the knowledge of the bryophyte flora of Maranhão and the Brazilian Cerrado. The collections were carried out in the months of February, June 2023 and January 2024, each excursion lasting five days, exploring the environments of cerrado, vereda and riparian forests (gallery and riparian forest). From 1,416 specimens collected, 64 species, 36 genera and 21 families of bryophytes were identified. Mosses predominated in the PEM with 14 families, 21 genera and 38 species, while liverworts were represented by seven families, 15 genera and 26 species. No hornworts were collected. There were eight new records for Maranhão, with one new record for the Brazilian Cerrado. Through this study, 51 species not yet recorded in the area were recorded. As expected, riparian forests stood out with the largest number of species and specimens, followed by vereda and cerrado. In relation to substrates, there was a predominance of corticolous species, followed by epiphyte, terrestrial, rupicolous, over termite mounds, and epiphyllous species. Liverworts showed a greater preference for trunks, while mosses preferentially colonized rocks. The predominance of bryophytes in riparian forests reinforces the importance of maintaining this environment for bryophyte communities in the Cerrado and the importance of PEM for conservation of the Cerrado’s biodiversity in Maranhão.